2004
DOI: 10.1016/j.jacc.2004.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic dysfunction in type 1 diabetes

Abstract: Augmented cardiac sympathetic tone and responsiveness and impaired myocardial perfusion may contribute to myocardial injury in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 154 publications
(54 citation statements)
references
References 39 publications
2
50
0
2
Order By: Relevance
“…13 Our group reported prior associations between CAN and diastolic dysfunction in patients with T1DM and mild microangiopathy. 2 Furthermore, sympathetic hyperinnervation in proximal myocardial segments coupled with denervation in distal segments has been observed in prior studies of diabetics with demonstrated autonomic neuropathy, and has been postulated to result in vascular hyperreactivity, paradoxical vasoconstriction, and potential arrhythmogenesis. 19 Studies of myocardial oxidative metabolism and substrate utilization have reported increased oxygen consumption in T1DM subjects as compared with normal controls, although this difference was no longer significant after correction for the rate pressure product.…”
Section: Discussionmentioning
confidence: 94%
“…13 Our group reported prior associations between CAN and diastolic dysfunction in patients with T1DM and mild microangiopathy. 2 Furthermore, sympathetic hyperinnervation in proximal myocardial segments coupled with denervation in distal segments has been observed in prior studies of diabetics with demonstrated autonomic neuropathy, and has been postulated to result in vascular hyperreactivity, paradoxical vasoconstriction, and potential arrhythmogenesis. 19 Studies of myocardial oxidative metabolism and substrate utilization have reported increased oxygen consumption in T1DM subjects as compared with normal controls, although this difference was no longer significant after correction for the rate pressure product.…”
Section: Discussionmentioning
confidence: 94%
“…One of them is impaired coronary flow reserve. EAT is associated with poor coronary flow reserve even in patients with angiographically normal coronary arteries [24]. Indeed, a strong relationship between impaired endothelial coronary flow reserve and IVRT time and LVDD was shown in two recent studies in uncomplicated hypertension and type 1 diabetic patients free of CAD [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pre-clinical [36–40] and clinical [15, 41, 42•, 43, 44] studies demonstrate a pathogenic role for inflammation, especially cytokine and chemokine production, in the DN and CAN disease course.…”
Section: Inflammation and Diabetic Neuropathymentioning
confidence: 99%